2019
DOI: 10.1016/j.ajog.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Contraction of the levator ani muscle during Valsalva maneuver (coactivation) is associated with a longer active second stage of labor in nulliparous women undergoing induction of labor

Abstract: BACKGROUND: The Valsalva maneuver is normally accompanied by relaxation of the levator ani muscle, which stretches around the presenting part, but in some women the maneuver is accompanied by levator ani muscle contraction, which is referred to as levator ani muscle coactivation. The effect of such coactivation on labor outcome in women undergoing induction of labor has not been previously assessed. OBJECTIVE: The aim of the study was to assess the effect of levator ani muscle coactivation on labor outcome, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 55 publications
(17 reference statements)
1
46
0
Order By: Relevance
“…We believe that fetal head movement upwards in the birth canal during pushing can be explained by levator ani muscle coactivation instead of relaxation. The effect of coactivation on labor has been assessed recently. Youssef et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that fetal head movement upwards in the birth canal during pushing can be explained by levator ani muscle coactivation instead of relaxation. The effect of coactivation on labor has been assessed recently. Youssef et al .…”
Section: Discussionmentioning
confidence: 99%
“…and Kamel et al . examined nulliparous women at term before onset of labor and before induction of labor, respectively, and showed that women with coactivation had a significantly longer second stage of labor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few data have shed the light on the role of the pelvic floor in the mechanism of birth 16,20 . Smaller pelvic floor dimensions were found to be associated with a longer second stage of labor, whereas the relationship between pelvic floor dimensions and the mode of delivery is less clear with conflicting data 15‐17,21,22 . The proportional change of the ADP of the levator hiatus has been found to be a reproducible indicator of pelvic floor contraction 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pelvic floor muscle relaxation seems essential for childbirth. LAM coactivation was recently found to be associated with longer second, active second stage of labor and with less engaged fetal head at term 15,17,22 . In a recent study conducted on women undergoing vacuum delivery, LAM coactivation was assumed to be the cause of lack of fetal head descent with maternal pushing 23 …”
Section: Discussionmentioning
confidence: 99%